(3JfHjg GdNdGf Ydi HYV aVGFd QeVGfs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi SjOfG eMeO hBdg hUMHg CLeYjf bGd Gddg JYGdi (B" (3TgQ QeVGf GdPi CfRd ajg GdbQBf gOi ddfGS (B" (3Sei GdTgQ TgQ dTgQJg hefg TgQ adGf Sjag s
(3BNQgG (B:s
(3hPcQJ ai TQM efXheI GdCLghQi ai aVGFdg eG jajO GdWGdH aGfXQ Pdc ajg JaR HCMSf GdeWGdH hgPG BNQ eG CQOJ PcQg ai gPg GdQSGdI JHQckG HgG GdTgQ GdeYXe hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3JUhas
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs